Women on Boards of Directors: Causes and Consequences of Gender Composition in UK Listed Firms - Ioannou, Neophyta (2017)
The purpose of this study is to examine the relationship between the presence of women directors on corporate boards and the financial performance of the top 100 British listed companies for the year 2015. After the global financial crisis, the role of the board of directors has become even more important, as having major responsibility for recognising and managing all the types of risks. The companies seek to achieve a more sound risk management framework; thus, the gender composition in the boardrooms plays a significant role, due to their different opinions, abilities, and preferences related to risk. The steady increase of women in top leadership positions in recent years has made this research even more interesting. In particular, this research examined the hypothesis whether the highest presence of women directors will lead to a higher P/E ((share price)/(earnings per share) ) ratio. This examination was based on the top UK FTSE 100 firm boards in 2015. More specific, the sample included the 100 companies in the UK with the highest market capitalisation and performance in the British stock market, which are originated from various types of the industrial sector. This study concludes that there is an obvious conflict between the theory and market evidences. In particular, the theory argues that women are more risk averse than men, resulting in higher P/E ratio and less risky companies. However, market tends to underestimate companies that include women directors and considers these companies as riskier than others. This research suggests that the simplest explanation about the presence of women directors and the financial performance of companies is given by the theory due to the unusual presence of high proportions of women in corporate boardrooms. Additionally, it contributes to further improvement of the literature, because it demonstrates that the investors have the opportunity to invest in companies which have women directors in their boardrooms, because they will lead to the share prices’ increase, thus, they will gain a potential profit. Therefore, this decision by investors could be the beginning for the promotion of gender equality in corporate boards of directors.